Impact of Chronic Psychosocial Stress on Autonomic Cardiovascular Regulation in Otherwise Healthy Subjects - Lucini, Daniela; Di Fede, Gaetana; Parati, Gianfranco; Pagani, Massimo (Hypertension (Dallas, Tex. 1979), 2005)
Elevated psychosocial stress might favor the occurrence of cardiovascular disease; however, mechanisms are incompletely understood. We hypothesized that patients (n=126; 44±1 years of age) referred to an internal medicine clinic because of symptoms related to chronic psychosocial stress would demonstrate signs of autonomic dysregulation compared with controls (n=132; 42±1 years of age). We used autoregressive spectral analysis of RR interval variability to obtain indirect markers of sympathetic and of vagal (respectively, low-frequency and high-frequency components, both expressed in normalized units) oscillatory modulation of sinoatrial node, as well as of sympathetic vasomotor regulation (low-frequency component of systolic arterial pressure variability) and of cardiac baroreflex sensitivity (α-index). Higher values of systolic and diastolic arterial pressure (respectively, 124±1 versus 117±1 mm Hg and 80±1 versus 75±1 mm Hg; both P<0.001), altered markers of autonomic regulation (increased normalized low-frequency and reduced high-frequency component of RR variability, P<0.005; increased-low frequency component of systolic arterial pressure variability, P<0.002), and reduced baroreflex sensitivity (19.3±1.4 versus 23.0±2.0 ms/mm Hg; P<0.05) were observed in patients compared with controls. Autonomic responses to active standing were also blunted in stressed patients. Autonomic markers were significantly correlated to stress perception score and were capable of discriminating between controls and patients with a high degree of accuracy. Chronic real-life stress in humans appears associated to increased arterial pressure and to impaired autonomic regulation of cardiovascular functions. The combination of sympathetic predominance, vagal withdrawal, and blunted baroreflex sensitivity might represent a treatable mechanistic link between psychosocial factors and future incidence of hypertension.